The Influence of Audit Opinion and Audit Tenure on Audit Report Lag in Property and Real Estate Companies Listed on the Indonesian Stock Exchange in 2021-2023 - Anisa Shafa Aunur Rozana; Srihadi Winarningsih (SEAN Institute, 2024)
Audit report lag is the time span in days from the end date of the company's fiscal year to the date stated in the auditor's report. This research aims to find out how much influence profit and loss, audit opinion and audit tenure have on audit report lag in Property and Real Estate companies on the Indonesia Stock Exchange in 2021 - 2023. The sampling method in this research uses a purposive sampling technique, there are 99 samples selected. will be used in this research. This research uses panel data regression analysis techniques for data processing using Eviews 12 software. The results of hypothesis testing in this research show that (1) then audit opinion has an effect on audit report lag (2) and finally audit tenure has an effect on audit report lag.